Production of the Global Health Doctor: Discourses on International Medical Electives - Lori Hanson; Jethro Cheng (Engaged Scholar Journal, 2018)
This article attempts to interrupt dominant narratives in the literature about international service-learning (ISL) in the field of medicine by critically deconstructing discourse related to a common model used to teach global health in undergraduate medical education: the international medical elective (IME). Based on a study conducted in 2012, the results have not been previously published. Using a Foucauldian discourse analysis, the study interrogated the underlying assumptions behind the nature of “service” being rendered by conveying the imagery, language, and consequences of the dominant discourses used in journal articles indexed on MEDLINE between 2000 and 2011. The analysis revealed an IMEs literature steeped in problematic discursive (re)productions of colonial constructs and imagined geographies, primarily through two dominant discourses designated as “disease and brokenness” and “romanticizing poverty.” These discourses both justify and reinforce privileged subject positions for students engaged in these ISL experiences, while inadequately considering structures and systems that perpetuate marginalization and health inequities. Such discourses often marginalize or essentialize people of so-called “host” countries, while silencing subaltern perspectives, resistance struggles, knowledges, and epistemologies. Challenging current ISL practices in medicine requires educators to actively work towards decolonialization, in part by recognizing the ability of discourses to produce meaning and subjects.